Career success factors of women engineers in leadership positions - Miriam Schmitt (Journal of Applied Leadership and Management, 2020)
Research questions: Which factors explain the career success of women engineers in leadership positions? Methods: This study conducted qualitative semi-structured interviews with women engineers in Germany who hold leadership positions in industry. The interview questions focused on these women's career paths into leadership positions, along with any conducive or impeding factors. The interview data was analyzed using qualitative content analysis. Results: The results show that the interdependence of the success factors on the individual and contextual levels contributes to women engineer's career advancement to leadership positions. These women are motivated by an intrinsic interest in technical tasks and career orientations towards responsibility, autonomy, and challenges. Their self-efficacy expectations help them to pursue their career interests, to cope with gender-specific barriers, and to adapt to the work environment. Furthermore, these women are focused on career goal setting and they apply career strategies such as proactive self-marketing and networking. On the contextual level, these women receive social support from their supervisors, colleagues, and husbands, which helps them to manage their careers and achieve leadership positions.
Keywords: 650